"Try Walking in Our Shoes": Teaching Acculturation and Related Cultural Adjustment Processes Through Role-Play. (July 2016) - Zamboanga, Byron L.; Ham, Lindsay S.; Tomaso, Cara C.; Audley, Shannon; Pole, Nnamdi
In this article, we describe several role-playing exercises on acculturation and relevant cultural adjustment processes that we incorporated into Tomcho and Foel's classroom activity on acculturation, and we report data that examine subsequent changes in students' responses on pretest and posttest measures shortly after the activity and present qualitative themes derived from students' reflections taken from an assignment at the end of the semester. We found no increases in students' perceptions that role-playing can help them gain a better understanding of acculturation. However, there were increases in students' awareness that acculturation is a real-world phenomenon, their understanding of how acculturation can impact people's lives, and their sensitivity and empathy for people who face some of the challenges associated with acculturation, even after controlling for students' pretest level of interest in cultural issues. Furthermore, thematic analyses indicated that students learned some of the challenges associated with acculturation and were able to label personal experiences associated with acculturation. They also gained concrete knowledge about and in-depth realization of the concept of acculturation. Instructors who teach psychology classes can use this exercise to complement traditional methods of teaching.